2020
DOI: 10.1038/s41598-020-67301-1
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid improves feto-placental and offspring metabolic outcomes in hypercholanemic pregnancy

Abstract: Perturbations in the intrauterine environment can result in lifelong consequences for metabolic health during postnatal life. Intrahepatic cholestasis of pregnancy (ICP) can predispose offspring to metabolic disease in adulthood, likely due to a combination of the effects of increased bile acids, maternal dyslipidemia and deranged maternal and fetal lipid homeostasis. Whereas ursodeoxycholic acid (UDCA) is a commonly used treatment for ICP, no studies have yet addressed whether it can also prevent the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…The elevated serum bile acids that form the core phenotype are also associated with maternal and fetal dyslipidemia 46 48 , and increased rates of gallstone formation 49 . Variation at ABCG8 has previously been linked to gallstone disease and other lipid-related phenotypes 50 , 51 .…”
Section: Resultsmentioning
confidence: 99%
“…The elevated serum bile acids that form the core phenotype are also associated with maternal and fetal dyslipidemia 46 48 , and increased rates of gallstone formation 49 . Variation at ABCG8 has previously been linked to gallstone disease and other lipid-related phenotypes 50 , 51 .…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Dann et al, UDCA treatment did not alter maternal plasma lipid concentrations 16 . However, a recent study revealed that UDCA treatment could ameliorate ICP‐associated fetal dyslipidemia 37 . Further animal models have confirmed that UDCA treatment in cholestatic pregnancy can induce hepatoprotective mechanisms in the fetal liver and improve glucose tolerance in adult offspring 37 .…”
Section: Discussionmentioning
confidence: 98%
“…However, a recent study revealed that UDCA treatment could ameliorate ICP‐associated fetal dyslipidemia 37 . Further animal models have confirmed that UDCA treatment in cholestatic pregnancy can induce hepatoprotective mechanisms in the fetal liver and improve glucose tolerance in adult offspring 37 . UDCA may improve metabolic outcomes in ICP pregnancies, supporting the effectiveness of UDCA treatment in women with ICP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the perinatal effects, long-term effects are also suspected. For example, it has recently been shown that treatment with UDCA has a favourable effect on fetal lipid metabolism [134]. UDCA treatment is safe and has few side effects [127].…”
Section: Ursodeoxycholic Acid (Udca)mentioning
confidence: 99%
“…Neben den perinatalen Effekten werden auch langfristige Auswirkungen vermutet. So konnte kürzlich der Nachweis erbracht werden, dass die Behandlung mit UDCA den fetalen Lipidstoffwechsel günstig beeinflusst 134 .…”
Section: Ursodeoxycholsäure (Udca)unclassified